Energy Optimal Configuration Strategy of Distributed Photovoltaic Power System for Multi-Level Distribution Network - Yanmin Wang; Hanqing Zhang; Weiqi Zhang; Song Han; Yuzhuo Yang (Applied Sciences)
As the strategic position of distributed photovoltaic (PV) power generation in multi-level distribution networks continues to rise, its impact on the stable operation of the grid is becoming increasingly significant. This study delves into the influence of two key factors, the integration location and penetration rate of PV systems, on the distribution and flow of energy and the steady-state performance of multi-level distribution networks. Based on this, the study proposes a simplified grid analysis framework for analyzing and optimizing the energy allocation strategy of distribution systems and develops a PV configuration strategy aimed at optimizing the energy planning and design process of engineering projects. Taking a typical PV-participating distribution system as an example, the study provides a detailed description of the typical three-layer distribution network structure and deduces the relationship of the PV, node voltage, and node voltage deviation. The study verifies the accuracy and practical value of the proposed simplified framework through real-time monitoring simulation of node voltages and line losses. Finally, to achieve optimal energy allocation, the study proposes a PV segmentation strategy applied to the system and compares it with the traditional reactive power control strategy, demonstrating the advantage of the strategy in improving the system’s clean energy ratio and reducing network losses. This paper’s research on the impact of PV systems and the proposed simplified theory for distribution networks is universally applicable, and it holds significant reference value for practical engineering design.